Analisis Budaya Organisasi Pemerintah Daerah (Pemda) di Era Otonomi Daerah - Pramudhietha, Gilang (Universitas Muhammadiyah Surakarta, 2017)
Organization is a forum cooperation of a group? individuals to achieve a goal it has set the vision and mission of the organization. To achieve the desired results required a commitment and a good organizational culture so that it can have a positive impact for the members of the organization and also for the institution in question. Organizational culture is the glue between members, therefore, an organization must have a strong culture, and commitment in line with the collective confidence to improve its ability to compete globally. The purpose of this study was to determine and describe the organizational culture of the local government in regional autonomy. This study uses qualitative descriptive method using data analysis techniques model of Miles and Huberman. Data was obtained through interviews with five respondents who are employees in the public relations department of the Regional Secretariat Wonogiri. The results showed that organizational culture is a type of culture of the local government hierarchy which can not be separated from regulation, policy, law, and control of government agencies. Organizational culture in the public relations department is dynamic and the culture that appears is a work culture that requires employees to work in a professional manner.